2019
DOI: 10.1155/2019/5416728
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenases: Cellular Multifunctional and Protective Molecules against UV-Induced Oxidative Stress

Abstract: Ultraviolet (UV) irradiation can be considered as a double-edged sword: not only is it a crucial environmental factor that can cause skin-related disorders but it can also be used for phototherapy of skin diseases. Inducible heme oxygenase-1 (HO-1) in response to a variety of stimuli, including UV exposure, is vital to maintain cell homeostasis. Heme oxygenase-2 (HO-2), another member of the heme oxygenase family, is constitutively expressed. In this review, we discuss how heme oxygenase (HO), a vital rate-lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 148 publications
1
36
0
Order By: Relevance
“…As already described, the accumulation of ROS triggers the ER stress, which leads to a disturbance in the function of ER and accumulation of misfolded proteins [57]. The unfolded protein response (UPR), a cell protection program, is initiated to reduce the production of misfolded proteins and to finally extend the life span [58].…”
Section: Discussionmentioning
confidence: 99%
“…As already described, the accumulation of ROS triggers the ER stress, which leads to a disturbance in the function of ER and accumulation of misfolded proteins [57]. The unfolded protein response (UPR), a cell protection program, is initiated to reduce the production of misfolded proteins and to finally extend the life span [58].…”
Section: Discussionmentioning
confidence: 99%
“… 39 HO-1 is currently recognized as a potential antioxidant that may be effective in protecting against oxidative stress. 40 , 41 To explore the cytoprotective effects of HO-1 against oxidative stress due to CuNP-induced damage, hemin was used to induce HO-1 overexpression in vitro. We found that the induction of HO-1 increased antioxidant defenses and decreased ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq analysis was used to investigate the molecular mechanisms involved in WHT-mediated antioxidant effects. Based on the result from the canonical pathway and upstream regulator analysis by IPA, HMOX1 was identified is an important rate-limiting enzyme in heme catabolism and widely distributed in mammalian tissues, which not only is an oxidative stress marker but also has some cytoprotective properties [31]. It has been shown that HMOX1 knockout mice produced oxidative tissue injury and chronic inflammation [32].…”
Section: Discussionmentioning
confidence: 99%